Parental Roles In Preschool Children on the level Hospitalization Stress - Ardiyanti, Yulia; Fajar Sri Purwani; Eka Listiana; Siti Aminah; Mardliyah (HealthCare Nursing Journal, 2025)
Preschool children are children aged between 3-6 year. Number child Sick with various problem disease the more increase so that the need for child care in hospital. Problems that occur in children when hospitalized and experiencing the stress of hospitalization. The role of parents can prevent impact hospitalization on child. Study This aiming For to know the relationship between the role of parents and the stress of hospitalization of children after preschool in room Fatima House Sick Darul Consistency Kendal.  Design study use Descriptive Correlational, taking sample use Total Sampling. The sample in this study was 36 children, the research instrument was questionnaire and using the Depression Anxiety Stress Scale (DASS) questionnaire, data using the Spearman Correlation Test.  The results of the statistical analysis test using The Spearman test shows a p value of 0.047, this value is smaller than 0.05, which means Ha accepted means there is the relationship between inpatient stress levels and the role person old age in preschool children at Darul Istiqomah Hospital, Kendal.  From these results, it can be suggested that it can be useful as a source of information. for the community and input from nurses in providing outreach to parents and support full on child Which perform maintenance hospitalization